KITAB MIZAN AL-QARB (Telaah Metode Penentuan Awal Bulan Qamariah) - Nailur Rahmi; Yusri Akhimuddin (Institut Agama Islam Negeri Batusangkar, 2019)
The phenomenon of determining the time of the first day of Ramadan and the first day of Shawwal in Indonesia raises a prolonged folemic, each group has its own basis and methods. In West Sumatra region, there is a Tariqat Syatahariyah group which still has a large influence in the midst of the Minangkabau community, so they have their own method of determining the beginning of the Islamic month, the reckoning taqwim method. This method is found in the book of Mizan al-Qarb, which discusses the initial determination of the Qamariyah (lunar) system. This paper is more focused on how the dating system and the method of determining the beginning of the month of Qamariyah in the Mizan al-Qarb manuscript from the viewpoint of Falak and Astronomy. The method used is the field method and literature with the approach of Philology, Falak Science and Astronomy. The data source is the manuscript of Mizan al-Qarb found in Surau Calau Sijunjung. The documentation technique is used in data collection, with several stages: collection, selection, and criticism. With the findings of the manuscript Mizan al-Qarb with conditions that have begun to be damaged, then it is necessary to preserve the contents contained therein concerning the calendar and the method of determining the beginning of the Qamariyah which refers to the rukyat method, using the naked eye and not using the media, so it is concluded if the calculation starts from Thursday the result is the same as contemporary reckoning, if it starts Wednesday will be the first day difference with contemporary reckoning